Do You Transfer Your Skills? From Sports to Health Management in Cancer Patients - Sebri, Valeria; Savioni, Lucrezia; Triberti, Stefano; Durosini, Ilaria; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2020)
Skill transfer is a process in which cognitive and behavioral abilities are applied in another context different from the one in which they were originally learned. Literature demonstrated that this transferability is possible; studies highlight the application of skills from sport to other life-domains (e.g. school, work, health management) with the aim to improve individual characteristics and reach personal goals. Some factors such as positive communication, adequate context, a person-centered perspective and specific strategies are necessary. The objective of the present contribution is to explore the connection between sport and health management skills to enhance the coach/athlete relationship as well as the patient/physician one. Useful strategies of skills transfer from sport to cancer management are shown.